Dimerization and N-terminal domain proximity underlie the function of the molecular chaperone heat shock protein 90 - Chadli, Ahmed (The National Academy of Sciences, 2000)
Heat shock protein (hsp)90 functions in a complex chaperoning pathway where its activity is modulated by ATP and by interaction with several co-chaperones. One co-chaperone, p23, binds selectively to the ATP-bound state of hsp90. However, the isolated ATP-binding domain of hsp90 does not bind p23. In an effort to identify the p23-binding domain, we have constructed a series of hsp90 deletion mutants fused with glutathione-S-transferase (GST). Full-length GST-hsp90 is able to bind p23, and also, to chaperone assembly of progesterone receptor complexes. Truncations from the C terminus of GST-hsp90 reveal a C-terminal boundary for the p23-binding domain at approximately residue 490. This fragment contains, in order, the ATP-binding domain, a highly charged region, and 203 residues beyond the charged region. p23 binding is unaffected by deletion of the charged region, indicating that two noncontiguous regions of hsp90 are involved in p23 binding. These regions are only effective when hsp90 is in a dimeric state as shown by loss of p23 binding upon removal of GST or as shown by use of FK506-binding protein12-hsp90 constructs that form dimers and bind p23 only in the presence of a bivalent drug. Thus, p23 binding requires an hsp90 dimer with close proximity between N-terminal regions of hsp90 and a conformation specified by ATP.